Method of coordinate corrections by establishment the GPS virtual reference stations - Jonas Skeivalas; Silvija Gečytė (Geodesy and Cartography, 2012)
Creation of GPS virtual reference station by the method of coordinate corrections is analysed in the paper. The model is formed in the form of virtual reference station (VRS), when the precise coordinates of station are determined as mean value of GPS reference stations precise coordinates. Coordinate corrections of VRS station of virtually measured coordinates are obtained as mean or weighted mean values of coordinate corrections measured at GPS reference stations. The user of GPS receiver is correcting the measured coordinates by corrections computed from VRS broadcast coordinate corrections.